Acontecimiento vital estresante y trastorno de adaptación en una adolescente - Torres Yépez, Alba Nataly (2019)
The present case study has as its theme: “Stressful vital event and adaptation disorder in an adolescent”, precisely with the objective of evaluating these events through psychological exploration and how it influences the development of the adaptation disorder. For its development and obtaining results, different psychological tools were used such as the Observation guide, clinical history; STAI Questionnaire, Kovacs Depression Inventory and the Josep Font Family Test, who collaborated in the diagnosis of the disorder that afflicted the adolescent. As a solution to the problem, a therapeutic scheme was formulated with a focus on cognitive-behavioral techniques, aimed at improving the emotional-emotional area, as well as in social relationships, which produced significant and positive changes in the behavior and mood of the patient, despite the non-conclusion due to absenteeism to therapeutic sessions